Análise do comportamento mecânico e estudo do efeito de maclação mecânica do aço 316 LV sob estados de tração e compressão - Corrêa, Leonardo Muthi (2022)
The design of new steels with high yield, ultimate strength and good ductility is one of the desirable goals of the industry. The ultra-high strength steels with twin induced plasticity (TWIP) effect are used in applications that demand high ultimate strength, tenacity and use at cryogenic temperatures. Nevertheless, the knowledge of the mechanical behavior of this class of materials under different load conditions is still an object of research. Austenitic stainless steels attend to this classification. In this work the mechanical behavior of a 316LV austenitic stainless steel was evaluated in tension and compression at different temperatures (-100 a 300 ºC) and strain rate of 10-3. The results of the mechanical tests were correlated to the microstructural transformations through evaluation by optical microscopy, x-ray diffraction and electron backscattered diffraction (EBSD) maps. The influence of temperature and strain rate on the mechanical twinning mechanism was analyzed. Based on the results, it was possible to propose a constitutive model proposed to predict the mechanical behavior